Molecular survey of Candida species isolated from candiduria and its risk factors in adolescent - Sina Mohammadnejad; Mahsa Fattahi; Saeideh Hashemi-Hafshenjani; Maryam Roudbary; Shirin Farahyar (The Microbe)
Urinary infections, especially in patients with severe diseases, are common. The present study was performed to raise awareness about the frequency of Candida)C) species (spp.) and evaluated risk factors of candiduria in adolescents. This cross-sectional study was conducted on 114 urine samples from patients with suspected urinary tract infections referred to the Rasoul-e-Akram Educational Hospital of Iran University of Medical Sciences (Tehran, Iran). Urine samples were examined on a microscopic slide, and for colony count and observation of co-infections, the specimens were cultured on CHROMagar Candida medium. Molecular identification of Candida at the species level was done using the PCR-sequencing approach on the internal transcribed spacer (ITS) regions. Of the 114 admitted patients, 43 cases (37.7 %) had positive for Candida spp. The typical clinical isolates were C. albicans, C. tropicalis, C. parapsilosis, and C. glabrata. The study’s survey of predisposing factors revealed that 27 (62.8 %) had an underlying disorder and malignant diseases, including pneumonia, diabetes mellitus, sepsis, and leukemia; 20.9 % of the patients were treated with cancer drugs, and 20.9 % used antibiotics. Furthermore, indwelling urethral catheters were used in over 90.7 % of patients. These results highlight the current state of candiduria in hospitalized patients and provide a solid foundation for future research in this area, inspiring further investigation and potential breakthroughs.